Assessment of innovation activity of the regions of Russian Federation: methods, problems and prospects - Dzhalalov Rasim; Bugaeva Tatiana; Sumlikina Alina (π-Economy)
The innovative development of Russian regions plays a key role in ensuring economic resilience and enhancing competitiveness in the context of globalization and rapid changes driven by digital transformation. This article examines the influence of innovation on the socio-economic growth of regions, focusing on challenges, such as limited financial resources, insufficient coordination between research institutions and businesses, and uneven distribution of digital technologies and infrastructure resources. These challenges require the development of new methods for assessing and stimulating innovation activity aimed at overcoming existing barriers. For a more comprehensive assessment of regional innovative potential, a new methodology is proposed that includes not only traditional economic indicators, but also social, infrastructural, and technological factors. In contrast to conventional approaches, the proposed methodology allows a more precise evaluation of the impact of digital solutions, scientific research and innovation infrastructure on the processes that stimulate economic growth. This methodology allows regions to allocate resources more effectively, improve interaction between research institutions and businesses, and better adapt to global economic shifts and technological progress. The purpose of the study is to develop an approach for assessing the level of innovation activity in regions, taking into account current trends in digitalization, as well as institutional and human capital factors, while addressing identified methodological gaps. The article also presents a comparative analysis of existing methods for assessing innovation activity, highlighting their strengths and limitations. For the analysis, a system of indicators was used, combined into three groups: financial support for innovation, the state of the innovation environment and infrastructure, and the effectiveness of innovation. The collected data on the regions of Russia made it possible to identify successful strategies and approaches for promoting innovation that can be adapted by other regions to achieve sustainable and efficient development.